PENERAPAN KONSEP ERGONOMI DI PERPUSTAKAAN SMPN 22 KOTA TANGERANG SELATAN - Anggana, Aura Asta; Suryati, Adelina (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study was to find out how the application of the ergonomics concept affects the comfort of students in the library of SMPN 22 Tangerang Selatan, then to find out the obstacles to the application of the concept of ergonomics in the library of SMPN 22 Tangerang Selatan. The research was conducted on Monday, 13 June 2023 at 08:00 WIB at SMPN 22, South Tangerang City. The research method used is a qualitative method, the type in this study is descriptive research. The conclusion of this study is that the SMPN 22 Kota Tangerang Selatan library has been implemented and adapted to the ergonomic concept. The equipment in the library is quite adequate and the floor layout is adjusted to the room conditions. The number of rooms is adjusted to the needs and circumstances of the library itself.